Analysis Workload And Communication Effects On Employee Performance - Lussianda, Erfa Okta; Adrian, Muhammad; Anggraini, Nia; Fahrozi, Muhammad (Husnayain Business Review, 2024)
This study investigates the impact of analysis workload and communication on employee performance, focusing on Examination, Collection, Intelligence, and Investigation departments. Using a sample of 42 individuals, data was analyzed through descriptive and inferential statistics, including validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. Findings indicate that while workload does not significantly affect performance, communication does. The combined effect of workload and communication significantly influences performance, explaining 69.1% of its variability. Keywords: Workload, Communication, Performance.